Kelelahan Kerja pada Pekerja Rumput Laut di Kabupaten Takalar - Yahya Thamrin (Media Kesehatan Masyarakat Indonesia, 2020)
Fatigue is a common condition for all workers after doing their job One of the informal sectors that have not yet received adequate occupational health services is seaweed workers. This research aims to determine the relationship between age, working time, work period, work attitude, workload, and work process of workplace fatigue on seaweed workers in Takalar district. The type of this research is an analytical observational with a cross-sectional study approach. The samples in this study were 74 respondents using purposive sampling techniques. Data were obtained using the Work Fatigue Measurement Tool Questionnaire for fatigue and a Rapid Entire Body Assessment (REBA) Questionnaire sheet for work attitude. The Chi-Square test was used to analyze the relationship between variables. The results showed that workers experienced 27% working fatigue and 73% of workers did not experience work fatigue. As for the relationship between age (p=0.006) and work process (p=0.030) with work fatigue, and no relationship between the length of work (p=0.183), the working period (p=0.429), the working attitude (p=0.319), and the workload (p=0.080) with work fatigue. It is suggested that workers need to pay attention to have sufficient rest time and stretch in between jobs in order to prevent worker fatigue.